Health and economic impact of oral PrEP provision across subgroups in western Kenya: a modelling analysis - Linxuan Wu; Sarah Cox; Monisha Sharma; Brian Pfau; Rachel Wittenauer (BMJ Global Health)
Introduction Oral pre-exposure prophylaxis (PrEP) is a priority intervention for scale-up in countries with high HIV prevalence. Policymakers must decide how to optimise PrEP allocation to maximise health benefits within limited budgets. We assessed the health and economic impact of PrEP scale-up among different subgroups and regions in western Kenya.Methods We adapted an agent-based network model, EMOD-HIV, to simulate PrEP uptake in six counties of western Kenya across seven subgroups including serodiscordant couples (SDCs), adolescent girls and young women (AGYW), adolescent boys and young men, women with multiple partners and men with multiple partners. We modelled 5 years of PrEP provision assuming 90% PrEP uptake in the prioritised subgroups and evaluated outcomes over 20 years compared with a no PrEP scenario. All results are presented in 2021 USD$.Results Population PrEP coverage was highest in the broad AGYW scenario (8.3%, ~2 fold higher than the next highest coverage scenario) and lowest in the SDC scenario (0.37%). Across scenarios, PrEP averted 4.5%–21.3% of infections over the 5-year implementation. PrEP provision to SDCs was associated with the lowest incremental cost-effectiveness ratio (ICER), $245 per disability-adjusted life year (DALY) averted (CI $179 to $435), followed by women and men with multiple partners ($1898 (CI $1002 to $6771) and $2351 (CI $1 831 to $3494) per DALY averted, respectively). Targeted strategies were more efficient than broad provision even in high HIV prevalence counties; PrEP scale-up for AGYW with multiple partners had an ICER per DALY averted of $4745 (CI $2059 to $22 515) compared with $12 351 for broad AGYW (CI $7 050 to $33,955). In general, ICERs were lower in counties with higher HIV prevalence.Conclusions PrEP scale-up can avert substantial HIV infections and increasing PrEP demand for subgroups at higher risk can increase efficiency of PrEP programmes. Our results on health and cost impact of PrEP across geographic regions in western Kenya can be used for budgetary planning and priority setting.